OLAH RAGA DAN KADAR GULA DARAH PADA KELOMPOK LANSIA DENGAN DIABETES MELITUS DI WILAYAH KERJA PUSKESMAS ULAKAN TAHUN 2017 - Khairul Andri - (Menara Ilmu, 2018)
Exercise has a close relationship with blood sugar levels of older people with diabetes. Themonthly report of Puskesmas Ulakan recorded an incidence increase of pproximately 3.5%from January to February 2017. The purpose of this study was to determine the effect ofexercise and blood glucose level in older people groups with diabetes mellitus in PuskesmasUlakan Working Area in 2017. The research used One Group Pretes-Posttes design. The studyinvolved 15 older people with diabetes melitus in Ulakan Puskesmas Working Area. Theanalysis using T-test showed blood sugar level before exercise was 236,93 mg / dl withstandard deviation 14,523 mg / dl and after exercise was 169.40 mg / dl with standarddeviation 18,535 mg / dl and p value 0,000 means there is an influence of exercise on thedecrease in blood sugar levels in older people with diabetes mellitus. It is expected that thisresearch can be used by community nurses to socialize the use of exercise as a nonpharmacological treatment in order to control blood sugar levels in older people with diabetesmellitus.Keywords: older people, exercise, blood glucose level, diabetes mellitus